Entre a fé, a obra social e a publicidade: uma análise crítica do discurso da responsabilidade social da Igreja Universal do Reino de Deus - Oliveira, Derli Machado de (2013)
Situated on Applied Linguistics (PENNYCOOK, 1998; MOITA LOPES, 2003, 2006, 2008, 2009), this thesis, which is inscribed in a qualitative-interpretative approach of a critical analysis perspective , lies on the speech of social responsibility and the way like that is employed in seeking for legitimacy and prestige within the neopentecostal brazilian religious field, more specifically of the Universal Church of the Kingdom of God. The general goal of this research is t reflect upon the speech on social responsibility and the rethoric of selfpromotion of the Universal Church through the role of social actors in the making of his her identities, materialized in the newspaper Folha Universal. In order to achieve that, we have conjugated, in this research, social and discursive analysis. On the linguistic-discursive approach, the research is based on the Critical Analysis of Discourse (ACD), specially in Fairclough (2001, 2003, 2006), a proposal that provides theoretical-methodological tools to investigate the language beyond the linguistic structures , that is, the discourse, social practices in which it occurs and more ample structures. Theoretical assumptions were also used of Sistemico-Functional Linguistics(LSF), matching with categories of the Transitivity System of Halliday (1994, 2004), of the forms of representation of social actors in the socioeconomic perspective by Van Leeuwen (1997, 2008) and of the Appraisal system by Martin and White (2005). As we develop the argumentation on thesobre social role of religion in this thesis, we make use of the authors such as Freston (1994), Oro (1997, 2003), Campos (1996, 1999), Mariano (1999), Meneses (2008), among several ones. We have also used a series of concepts and categories coming from the field of communication and marketing on the business social responsability and social marketing . In this area, we take as references the contributions of Bueno (2003), Fossá and Sartoretto (2003) and Zenone (2006). The corpus of the work is framed by news taken at the newspaper Folha Universal, in which are given the social responsibility actions of the church . The timeframe used was on the editions of 2010 thru 2012. Results found at he analysis of the News lead to semantic features of Assessment of Affection, Judgment and Appreciation, many times followed by Gradation, and the Attribution, one of the subsystems of the Attachment, are evidence of positive assessments for the Universal Church and its agents and make up rethorical elements which provide structure for the discourse of the Universal Church at the newspaper Folha Universal consisted of its image (style) of social responsibility . Results show that the most frequente social actors of the discourse are, on one hand, the Universal Church itself and its volunteers, famous (actors, actresses, presenters), politicians and authorities, on the other hand, the population which was helped by the Church social projects . The first group seems to be Always activated, however the second one, most of the time rather passive. These are also represented by assimilation in most of the occurrences, however the other ones by individualization and nomination entitled by honorification, except for the volunteers that are represented either as an individual, or as a group